Effect of Fullerene Derivatives on the Lifetime Characteristics and the Stability of Inverted Perovskite Solar Cells - Askin, Neslihan Babayigit; Berber, Savas; Tumay, Tulay Asli; Alturk, Elif; Tekin, Emine (Japan Inst Metals & Materials, 2022)
This contribution demonstrates the effects of mole ratio, concentration of perovskite components and fullerene derivatives used as electron transport layer (ETL) on the stability and performances of inverted perovskite solar cells (PSCs). C60, C70, PC61BM and PC71BM are selected as ETL materials. Methylammonium iodide (MAI):Lead (II) iodide (PbI2):Lead(II) chloride (PbCl2) are used to form MAPb2I2Cl which is a mixed halogen perovskite structure. The fabricated perovskite device containing PCBM with optimized concentration and mole ratio gives high power conversion efficiency (PCE) of 9.07% with an open-circuit voltage (Voc) of 0.91 V, short circuit current density of 14.1 mA/cm2, and fill factor of 0.71. The lifetime characteristics and the stability are found significantly dependent on the fullerene type. The devices containing PC61BM and PC71BM are able to maintain 50% and 30% of its initial performances, respectively, even after 1100 hours. Overall, the obtained results represent an important step understanding the impacts on the p-i-n type perovskite lifetimes. [doi:10.2320/matertrans.MT-M2022056]
Keywords: perovskite solar cell; fullerene; electron transport layer; PCBM; lifetime